Orthodontic Management of a Palatal Fistula in a Patient With Pierre Robin Sequence Using 3D Intraoral Scanning and Computer-Aided Design. (November 2021) - Wang, Jue; Ho, Viet; Kau, Chung How
Pierre Robin sequence (PRS) is a rare congenital abnormality that may be classified as a first branchial arch syndrome. Patients with PRS who present with cleft palate have a deformity to the soft or hard palate of the maxilla that is repaired within the first year of birth. Despite the repair, patients may experience oronasal complications. Surgical repair is usually necessary if palatal fistula presents, and prosthetic obturators are used to provide temporary relief prior to surgery. This case report outlines the steps in the successful fabrication of a custom-fitted temporary vacuum-formed prosthetic obturator using computer-aided design technology to provide a more comfortable and effective treatment option for the patient.